2004
DOI: 10.1242/jcs.01236
|View full text |Cite
|
Sign up to set email alerts
|

Continuous phosphatidylinositol metabolism is required for cleavage of crane fly spermatocytes

Abstract: Successful cleavage of animal cells requires co-ordinated regulation of the actomyosin contractile ring and cleavage furrow ingression. Data from a variety of systems implicate phosphoinositol lipids and calcium release as potential regulators of this fundamental process. Here we examine the requirement for various steps of the phosphatidylinositol (PtdIns) cycle in dividing crane fly (Nephrotoma suturalis) spermatocytes. PtdIns cycle inhibitors were added to living cells after cleavage furrows formed and bega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 73 publications
3
54
0
Order By: Relevance
“…The hydrolysis of PtdIns(4,5)P 2 to inositol (1,4,5)-triphosphate [Ins(1,4,5)P 3 ] by PLC is similarly required to maintain the furrow (Emoto et al, 2005;Field et al, 2005b;Wong et al, 2005). Together, these findings are consistent with inhibitor studies in crane fly spermatocytes that suggest the requirement of continuous PtdIns metabolism for cytokinesis (Saul et al, 2004). A precise assessment of comparative functions of different phosphorylated forms of PtdIns in cytokinesis will require a more detailed analysis of furrow behaviour following the downregulation of other steps in the pathway, by using comparable technical approaches.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The hydrolysis of PtdIns(4,5)P 2 to inositol (1,4,5)-triphosphate [Ins(1,4,5)P 3 ] by PLC is similarly required to maintain the furrow (Emoto et al, 2005;Field et al, 2005b;Wong et al, 2005). Together, these findings are consistent with inhibitor studies in crane fly spermatocytes that suggest the requirement of continuous PtdIns metabolism for cytokinesis (Saul et al, 2004). A precise assessment of comparative functions of different phosphorylated forms of PtdIns in cytokinesis will require a more detailed analysis of furrow behaviour following the downregulation of other steps in the pathway, by using comparable technical approaches.…”
Section: Discussionsupporting
confidence: 73%
“…the PtdIns-cycling pathway has been described for cytokinesis of crane fly spermatocytes in a study using chemical inhibitors (Saul et al, 2004). Moreover, genetic studies have implicated the two kinases that successively phosphorylate PtdIns: in Drosophila the phosphatidylinositol 4-kinase (PI-4 kinase) four wheel drive (fwd) (Brill et al, 2000), and in S. pombe the phosphatidylinositol-4-phosphate 5-kinase [PI(4)P-5 kinase] (Cullen et al, 2000;Zhang et al, 2000), to produce PtdIns(4,5)P 2 as being required for cytokinesis.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium has been shown to be required for cytokinesis in several embryonic cell types (Fluck et al, 1991;Miller et al, 1993;Chang and Meng, 1995;Muto et al, 1996;Webb et al, 1997;Saul et al, 2004;Wong et al, 2005), and myosin activation (Shuster and Burgess, 2002a;Stack et al, 2006) as well as membrane addition (Shuster and Burgess, 2002a) are candidate downstream effectors. Imaging of calcium dynamics in dividing L. pictus eggs revealed that there is a mobilization of calcium at the metaphase-anaphase transition that is necessary for cytokinesis (Groigno and Whitaker, 1998), raising the possibility that this calcium transient may partially serve as the "timer" for the activation of myosin II.…”
Section: Precocious Activation Of Cortical Tension During Cell Divisionmentioning
confidence: 99%
“…296 Hydrolysis of PtdIns(4,5)P2 by phosphlipasec(PLC) yields inositol trisphosphate (IP 3 ), which stimulates calcium release from internal stores. Inhibitors of PLC can interfere with cytokinesis, 297 which can in some cases be rescued by addition of calcium. 298 Alternatively, PtdIns(4,5)P2 may play a direct role in recruiting membrane proteins required for stability of the furrow.…”
Section: Regulation Of Cytokinesis By Lipidsmentioning
confidence: 99%